Teachers’ Unions and Movements for Pedagogical Reform against Educational Neoliberalism: The Cases of Spain, Argentina and Chile (Foro de Educacion, 2019)
The present article analyses the conflicts between teachers’ unions and Movements for Pedagogical Reform MRP, acronym in Spanish), on one hand, and the educational neoliberalism implemented by the Governments of Spain, Argentina and Chile over the last four decades, on the other. It is aimed at learning the reasons that led these groups to oppose the advance of private education over public education in these three countries, which are historically and culturally similar, in addition to pointing out the limitations of their respective actions and to propose ways to overcome these factors. The method employed is historical-comparative in order to establish analogies and differences among the cases studied, using primary and secondary sources. The three examples of countries are analysed in chronological order based on the implementation of educational neoliberalism and the different types of government that promoted it. Subsequently, a comparison is made of their similarities and differences with a view to finding possible convergences in their development. By way of conclusion, taking into account the limitations of the MRPs’ and teachers’ unions’ protest actions in the respective countries, a proposal is developed from a holistic perspective designed to coordinate their actions supranationally in defence of public schools as opposed to private instruction.